BMSCs mediates endothelial cell autophagy by upregulating miR‐155‐5p to alleviate ventilator‐induced lung injury. Issue 7 (31st March 2022) - Lin, Xin; Yu, Tianxing; Luo, Jianxiong; Chen, Lin; Liu, Yang; Xu, Junping; Chen, Lifang; Lin, Qiong; Bao, Yuwang; Xu, Liyu
Abstract: In this study, we explored to detect the effects and mechanism of bone‐marrow‐derived mesenchymal stem cells (BMSCs) on ventilator‐induced lung injury (VILI). We transplanted BMSCs in mice and then induced VILI using mechanical ventilation (MV) treatment. The pathological changes, the content of PaO2 and PaCO2, wet/dry weight ratio (W/D) of the lung, levels of tumor necrosis factor‐α and interleukin‐6 in bronchoalveolar lavage fluid, and apoptosis were detected. The autophagy‐associated factor p62, LC3, and Beclin‐1 expression were analyzed by western blot. The quantitative polymerase chain reaction was applied to detect abnormally expressed microRNAs, including miR‐155‐5p . Subsequently, we overexpressed miR‐155‐5p in VILI mice to detect the effects of miR‐155‐5p on MV‐induced lung injury. Then, we carried out bioinformatics analysis to verify the BMSCs‐regulated miR‐155‐5p that target messenger RNA. It was observed that BMSCs transplantation mitigated the severity of VILI in mice. BMSCs transplantation reduced lung inflammation, strengthened the arterial oxygen partial pressure, and reduced apoptosis and the W/D of the lung. BMSCs promoted autophagy of pulmonary endothelial cells accompanied by decreased p62 and increased LC3 II/I and Beclin‐1. BMSCs increased the levels of miR‐155‐5p in VILI mice. Overexpression of miR‐155‐5p alleviated lung injury in VILI mice following reduced apoptosis and increased autophagy. Finally, TAB2 was identified as a downstream target of miR‐155‐5p and regulated by miR‐155‐5p . BMSCs may protect lung tissues from MV‐induced injury, inhibit lung inflammation, promote autophagy through upregulating of miR‐155‐5p .